A Combinatorial Geometric Mean

Calculus Level 5

Let G n G_n be the geometric mean of the following n + 1 n+1 combinations:

( n 0 ) , ( n 1 ) , ( n 2 ) , , ( n n ) . \displaystyle\binom{n}{0},\binom{n}{1},\binom{n}{2},\ldots,\binom{n}{n} .

Find lim n G n n \displaystyle \lim_{n\to \infty}\sqrt[n]{G_n} .

Give your answer to 3 decimal places.


The answer is 1.649.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

We have: ( n 0 ) ( n 1 ) ( n 2 ) ( n n ) = k = 0 n n ! k ! ( n k ) ! = k = 1 n ( n k + 1 ) n + 1 2 k \displaystyle\binom{n}{0}\binom{n}{1}\binom{n}{2}\ldots\binom{n}{n}=\prod\limits_{k=0}^{n}{\frac{n!}{k!\left( n-k \right)!}}=\prod\limits_{k=1}^{n}{{{\left( n-k+1 \right)}^{n+1-2k}}}

On the other hand, k = 1 n ( n + 1 2 k ) = 0 \sum\limits_{k=1}^{n}{\left( n+1-2k \right)}=0 or ( n + 1 ) k = 1 n ( n + 1 2 k ) = 1 {{\left( n+1 \right)}^{\sum\limits_{k=1}^{n}{\left( n+1-2k \right)}}}=1

Thus, ( n 0 ) ( n 1 ) ( n 2 ) ( n n ) = k = 1 n ( n k + 1 n + 1 ) n + 1 2 k = k = 1 n ( 1 k n + 1 ) n + 1 2 k \displaystyle\binom{n}{0}\binom{n}{1}\binom{n}{2}\ldots\binom{n}{n}=\prod\limits_{k=1}^{n}{{{\left( \frac{n-k+1}{n+1} \right)}^{n+1-2k}}}=\prod\limits_{k=1}^{n}{{{\left( 1-\frac{k}{n+1} \right)}^{n+1-2k}}}

This implies that G n = k = 1 n ( n k + 1 n + 1 ) n + 1 2 k n + 1 = k = 1 n ( 1 k n + 1 ) 1 2 k n + 1 \displaystyle G_n=\sqrt[n+1]{\prod\limits_{k=1}^{n}{{{\left( \frac{n-k+1}{n+1} \right)}^{n+1-2k}}}}=\prod\limits_{k=1}^{n}{{{\left( 1-\frac{k}{n+1} \right)}^{1-\frac{2k}{n+1}}}}

1 n ln G n = 1 n k = 1 n ( 1 2 k n + 1 ) ln ( 1 k n + 1 ) lim n 1 n ln G n = 0 1 ( 1 2 x ) ln ( 1 x ) d x \begin{aligned} & \Rightarrow \frac{1}{n}\ln {{G}_{n}}=\frac{1}{n}\sum\limits_{k=1}^{n}{\left( 1-\frac{2k}{n+1} \right)\ln \left( 1-\frac{k}{n+1} \right)} \\ & \Rightarrow \underset{n\to \infty }{\mathop{\lim }}\,\frac{1}{n}\ln {{G}_{n}}=\int\limits_{0}^{1}{\left( 1-2x \right)\ln \left( 1-x \right)dx} \\ \end{aligned}

Applying integral by part, we get: 0 1 ( 1 2 x ) ln ( 1 x ) d x = lim a 1 0 a ( 1 2 x ) ln ( 1 x ) d x = 1 2 \displaystyle\int\limits_{0}^{1}{\left( 1-2x \right)\ln \left( 1-x \right)dx}=\underset{a\to {{1}^{-}}}{\mathop{\lim }}\,\int\limits_{0}^{a}{\left( 1-2x \right)\ln \left( 1-x \right)dx}=\frac{1}{2}

Hence, lim n 1 n ln G n = 1 2 lim n G n n = e 1.649 \displaystyle\lim_{n\to \infty }\frac{1}{n}\ln {{G}_{n}}=\frac{1}{2}\Rightarrow \lim_{n\to \infty }\sqrt[n]{{{G}_{n}}}=\sqrt{e}\approx\boxed{1.649}

Please explain the first step.

Saurabh Chaturvedi - 5 years, 4 months ago
Abhishek Sinha
Jan 29, 2016

Using Stirling's approximation of Binomial Coefficients , for 0 k n 0\leq k \leq n ( n k ) 2 n H ( k n ) \binom{n}{k} \sim 2^{nH(\frac{k}{n})} Where H ( ) H(\cdot) is the Binary Entropy function . Hence, G n n 2 1 n k = 0 n H ( k n ) ( a ) 2 0 1 H ( x ) d x = e , \sqrt[n]{G_n} \sim 2^{\frac{1}{n}\sum_{k=0}^{n}H(\frac{k}{n})}\stackrel{(a)}{\to} 2^{\int_{0}^{1}H(x)dx}=\sqrt{e}, where in (a) we have used the fundamental theorem of integral calculus.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...